Farm poems & seasons poems - Forster, John 2008; Foster, John, 1941 October 12- (Sea Girt, N.J. : Dingles & Company, 2008)
An illustrated collection of poems for children about farms and the seasons.
Children
Keywords: Farm life -- Juvenile poetry; Seasons -- Juvenile poetry; Children's poetry, American